Dynamic modulation of Dnmt2-dependent tRNA methylation by the micronutrient queuine. Issue 22 (30th September 2015) - Müller, Martin; Hartmann, Mark; Schuster, Isabelle; Bender, Sebastian; Thüring, Kathrin L.; Helm, Mark; Katze, Jon R.; Nellen, Wolfgang; Lyko, Frank; Ehrenhofer-Murray, Ann E.
Abstract: Dnmt2 enzymes are cytosine-5 methyltransferases that methylate C38 of several tRNAs. We report here that the activities of two Dnmt2 homologs, Pmt1 from Schizosaccharomyces pombe and DnmA from Dictyostelium discoideum, are strongly stimulated by prior queuosine (Q) modification of the substrate tRNA. In vivo tRNA methylation levels were stimulated by growth of cells in queuine-containing medium; in vitro Pmt1 activity was enhanced on Q-containing RNA; and queuine-stimulated in vivo methylation was abrogated by the absence of the enzyme that inserts queuine into tRNA, eukaryotic tRNA-guanine transglycosylase. Global analysis of tRNA methylation in S. pombe showed a striking selectivity of Pmt1 for tRNA Asp methylation, which distinguishes Pmt1 from other Dnmt2 homologs. The present analysis also revealed a novel Pmt1- and Q-independent tRNA methylation site in S. pombe, C34 of tRNA Pro . Notably, queuine is a micronutrient that is scavenged by higher eukaryotes from the diet and gut microflora. This work therefore reveals an unanticipated route by which the environment can modulate tRNA modification in an organism.